Pengembangan Usaha Produk Bersulam Tapis Pada Thasya Ethnic Di Bandar Lampung - Senna Enzovani; Siti Khoirina; Aura Dewi; Dinni Arini Putria Alfriani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Community Service Activities (PKM) carried out by lecturers and students from the Faculty of Business at Mitra Indonesia University were carried out in order to increase knowledge about business development at Thasya Ethnic. The PKM implementation team participated in the practice of making tissue holders and wall hangings which were part of Thasya Ethnic's production. The raw materials are prepared by the owner of the Thasya Ethnic, making it easier for us to carry out the PKM. As a result of this activity the PKM Team from the Faculty of Business, Universitas Mitra Indonesia, gained sufficient knowledge to participate in producing ethnic products made from tapioca combined with woven fabrics or synthetic leather. Innovations are continuously carried out to maintain the sustainability of products that continue to develop to cope with increasingly varied market demands.